2017
DOI: 10.1016/j.fertnstert.2016.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Continued existence of significant disparities in the technical practices of sperm morphology assessment and the clinical implications: results of a French questionnaire

Abstract: The survey reveals a marked lack of uniformity in French laboratories for performing sperm morphology assessment and in the use of the results by physicians. Regular quality control procedures and well-trained personnel, up to date with their training and conversant with the latest techniques as well as harmonized practices, are clearly indispensable. It is time for a consensus on the practice and interpretation of this particular test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Intracytoplasmic sperm injection (ICSI) subsequently has become the most effective treatment for infertility due to male factors (oligozoospermia, asthenozoospermia and teratozoospermia). Sperm morphology is more difficult to evaluate than sperm concentration or progressive motility, and there have been inconsistencies between different laboratories due to the subjective nature of the sperm morphological assessment (Gatimel, Mansoux, Moreau, Parinaud, & Léandri, 2017; Punjabi et al, 2016; Wang et al, 2014). With the progressive description of normal sperm and sperm abnormalities (Danis & Samplaski, 2019), the thresholds for the normal sperm morphology rate (NSMR) in different editions of the World Health Organization (WHO) laboratory manual for the examination of human semen have been revised over time; the NSMRs in the 3rd, 4th and 5th editions are ≥30% (World Health Organization 1992), >14% (World Health Organization 1999) and ≥4% (World Health Organization 2010) respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Intracytoplasmic sperm injection (ICSI) subsequently has become the most effective treatment for infertility due to male factors (oligozoospermia, asthenozoospermia and teratozoospermia). Sperm morphology is more difficult to evaluate than sperm concentration or progressive motility, and there have been inconsistencies between different laboratories due to the subjective nature of the sperm morphological assessment (Gatimel, Mansoux, Moreau, Parinaud, & Léandri, 2017; Punjabi et al, 2016; Wang et al, 2014). With the progressive description of normal sperm and sperm abnormalities (Danis & Samplaski, 2019), the thresholds for the normal sperm morphology rate (NSMR) in different editions of the World Health Organization (WHO) laboratory manual for the examination of human semen have been revised over time; the NSMRs in the 3rd, 4th and 5th editions are ≥30% (World Health Organization 1992), >14% (World Health Organization 1999) and ≥4% (World Health Organization 2010) respectively.…”
Section: Introductionmentioning
confidence: 99%
“…(Blanchard et al ., ) have shown that the David classification was not discriminant for the rate of fertilization by conventional IVF compared with assessment using the strict criteria in the computer‐assisted sperm analysis (CASA) system. According to a French survey, there is considerable heterogeneity not only in the different reference thresholds used, but also between laboratories that claim to use standardized values from the literature; 33.6% of them use inadequate reference values for their classification (Gatimel et al ., ). Concerning the definition of reference values, it has been suggested that each laboratory could define its own standards (Matson, ) in view of the wide range of variability related to the technique and the operator and because of the considerable heterogeneity in the methods used from one laboratory to another.…”
Section: Resultsmentioning
confidence: 97%
“…The question thus arises of whether it is clinically relevant to systematically evaluate specific abnormalities in fertility check‐ups. Most laboratories systematically count the different abnormalities, while 47.7% of clinicians interviewed do not take them into consideration (Gatimel et al ., ). This is probably due to the very moderate clinical relevance of these different abnormalities, apart from the rare monomorphic abnormalities syndromes.…”
Section: Resultsmentioning
confidence: 97%
“…An increased probability of error often results from lack of adherence to a standardized protocol for the various duties carried out in the andrology laboratory [1,27,28]. A 15-year study of 151 andrology laboratories in Belgium that underwent repeated external quality assessments and controls (EQA/C) revealed many areas for concern, the most notable being limited funding for laboratory training, highly variable frequency of SA performance per month, and completion of proper training courses by only 40% of laboratory staff at the beginning of the study.…”
Section: Lack Of Standardized Protocols Training and Quality Assuramentioning
confidence: 99%